Giant Morphological Change in Layered Microribbons Featuring Reversible Sliding of Stacking Layers. (10th November 2014) - Zhang, Yifan; Peng, Cheng; Zhou, Zichao; Duan, Ran; Ji, Hongwei; Che, Yanke; Zhao, Jincai
<x xml:space="preserve">Abstract</x> A light‐induced giant lateral or longitudinal morphological change in layered microribbons is reported. This morphological change originates from the directional sliding of the stacking layers with respect to one another between their polar surfaces, into which the photoexcited intermolecular non‐bonded distortion is translated. Upon exposure to an electron beam, the laterally displaced layers slide back to their original positions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>